Highly stable mode-locked fiber laser with graphene oxide-coated side-polished D-shaped fiber saturable absorber - Ahmad, Harith; Soltani, Soroush; Thambiratnam, Kavintheran; Yasin, Moh (Society of Photo-optical Instrumentation Engineers, 2018)
A highly stable mode-lock fiber laser with a thin film coating of graphene oxide (GO) nanoparticles on a D-shaped fiber is proposed and demonstrated. The GO-coated D-shaped fiber, which serves as the cavity's saturable absorber (SA), is fabricated by drop-casting GO nanoparticles on the smooth and consistently polished area of the D-shaped fiber made using a disk-polishing machine. Mode-locking is induced through the interaction of the evanescent field from the D-shaped fiber and GO nanoparticle layer. The cavity has a length of 12.5 m with a fundamental frequency of 16.5 MHz and operates in the anomalous dispersion regime. Stable soliton modelocking is obtained above a pump power of 76.6 mW, with a central lasing wavelength of 1555.7 nm and welldefined Kelly's sidebands. The generated pulses have a repetition rate of 16.5 MHz and pulse duration of 1.18 ps over a pump power range of 76.6 to 280.5 mW, with only minor fluctuations observed. A signal-to-noise ratio of 58.3 dB is computed, indicating a highly stable output. The proposed SA fabrication technique provides a simple, cost-effective, and consistent method of generating mode-locked pulses in fiber lasers.